2007
DOI: 10.1063/1.2799991
|View full text |Cite
|
Sign up to set email alerts
|

Observations of image contrast and dimerization of decacyclene by low temperature scanning tunneling microscopy

Abstract: Low temperature scanning tunneling microscopy studies revealed both monomer and dimer forms of decacyclene (DC) on atomically clean Cu(100) and Cu(111). The observed image contrast in DC is strongly bias dependent and also influenced by tip modifications. Alternatively, dimers appear solely as protrusions and are nearly bias independent. We provide evidence of both dimer formation and dissociation and suggest that two DC molecules stack by aligning their molecular planes in a parallel fashion with respect to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Changes of intralayer corrugation with bias have been reported in different situations. 33,34 For single molecules, a corrugation change with bias was reported that disappeared when molecules dimerized. 33 This is clearly not the case here, where the corrugation change happens for the high-coverage case.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes of intralayer corrugation with bias have been reported in different situations. 33,34 For single molecules, a corrugation change with bias was reported that disappeared when molecules dimerized. 33 This is clearly not the case here, where the corrugation change happens for the high-coverage case.…”
Section: ■ Discussionmentioning
confidence: 99%
“…33,34 For single molecules, a corrugation change with bias was reported that disappeared when molecules dimerized. 33 This is clearly not the case here, where the corrugation change happens for the high-coverage case. Another case was due to picking-up oxygen atoms by the STM tip.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Hydrogen atoms in the interior of the decacyclene unit sterically repel one another such that each naphthalene unit twists out of plane with respect to the central benzene ring, contorting the planar decacyclene core into either a 3D propeller or boat conformation. 32 The propeller conformation refers to the decacyclene core of HBDC having its naphthalene groups twist out of plane such that it resembles a propeller or the blades of a fan, and the boat conformation refers to the same propeller conformation but with one of the naphthalene groups twisted in the opposite direction such that it more closely resembles a boat. These flexible naphthalene units play a large role in the unique mechanical properties that are preserved after functionalization with tert-butyl units.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Here, a false color scale is used to emphasize the highest tert-butyl lobes, where there is a difference of 0.2 Å between the top of the red-tipped lobes and the white layer. Although full monolayers of decacyclene are not chirally separated, 32,39 it is proposed that the addition of tert-butyl groups to HBDC serves to amplify the chirality of the decacyclene core and serves as the conduit through which chiral recognition occurs. At monolayer coverage, HBDC exists as enantiopure domains as shown in Figure 3b, where domains I and II are the enantiopure terrace domains, A00 and B00, described as in matrix notation, respectively.…”
Section: ■ Methodsmentioning
confidence: 99%
“…The relative orientation of the molecules in these aggregates is therefore likely influenced by long-range dipole-dipole interactions, with hydrogen-bonding interactions further stabilizing the structure. Wesoloski et al [44] have revealed both monomer and dimer forms of decacyclene (DC) on atomically clean Cu(100) and Cu(111). They provide evidence of both dimer formation and dissociation and suggest that two DC molecules stack by aligning their molecular planes in a parallel fashion with respect to the surface.…”
Section: The Adsorption Configuration Of Ofms On Hopgmentioning
confidence: 99%